Principles and strategies of teaching: a skills approach - Garcia, Carlito D. (Mandaluyong City, 2005)
This book was written for the purpose of helping prospective teachers to learn the art of teaching. It is designed as college textbook for a three-unit course in teaching methods and strategies
Keywords: Teaching strategies